On the sources of forgetting in working memory: The test of competing hypotheses. - Barrouillet, Pierre; Uittenhove, Kim; Lucidi, Annalisa; Langerock, Naomi (Quarterly Journal of Experimental Psychology, 2018)
Whether forgetting from working memory (WM) is only due to interference or is also caused by temporal decay is still a matter of debate. In the present study, this question was examined using complex span tasks in which each memory item was followed by a series of processing episodes, the duration and number of which were varied. It is known that recall performance in these tasks depends on the cognitive load (CL) of concurrent processing conceived as the ratio between processing time and free time, higher CL resulting in lower spans. The decay-and-refresh hypothesis accounts for this effect by assuming that memory traces decay during processing but are refreshed during free time. This hypothesis predicts lower recall performance with longer processing episodes, but no effect of their number as long as CL remains constant. The interference-only hypothesis supposes that free time is used to alleviate the interference created by processing distractors. This hypothesis is potentially compatible with an effect of the duration of processing episodes through increased interference, but predicts a detrimental effect of their number. In three experiments, the recall pattern fitted the predictions of the decay-and-refresh hypothesis for verbal WM, but that of the interference-only hypothesis for visuospatial WM. Although the entire pattern of data is more easily accommodated by the decay-and-refresh hypothesis than by its interference-only contender, our results suggest that it is unwise to aim at identifying a unique source to a complex phenomenon like WM forgetting.